Krukenburg tumour: Role of 18F-FDG PET/CT in identifying the primary site - Sharjeel Usmani; Sarah Murad; Fareeda al Kandari; Muneera Al Maraghy (Journal of the Pakistan Medical Association, 2024)
Krukenberg tumours are a rare form of metastatic tumours of the ovary. They primary site is usually the gastro-intestinal system with the most common being gastric cancer. We present the case of a 35-year-old female coming in with a large pelvi-abdominal mass for investigation. This pelvic mass showed mild to moderate metabolic activity. 18F-FDG PET-CT was able to identify the primary gastric carcinoma. Subsequent histopathology confirmed this to be gastric adenocarcinoma with metastases to the ovary. Keywords: 18F-FDG PET-CT, metastatic gastric carcinoma, Krukenburg tumour.